2009
DOI: 10.4137/cmt.s2165
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Lamotrigine in Older Adults with Epilepsy and Co-Morbid Depressive Symptoms

Abstract: Lamotrigine is an oral well absorbed antiepileptic medication (AED) from the phenyltriazine class approved by the FDA in 1994 for the treatment of epilepsy and in 2003 for the treatment of bipolar disorder. For epilepsy it is used to treat partial seizures, primary and secondary tonic-clonic seizures, and seizures associated with Lennox-Gastaut syndrome. Lamotrigine is the only AED that treats the depressive as well as the maniac phases of bipolar disorders. It is important to consider lamotrigine adverse reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 104 publications
(138 reference statements)
0
6
1
Order By: Relevance
“…However, studies reported 10% of patients may develop skin rash to LTG which might be severe and life-threatening [10]. The incidence of skin rash with LTG therapy in this study was 7.48%, which is lower than the reported rate, probably because of the low doses and slow titration.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…However, studies reported 10% of patients may develop skin rash to LTG which might be severe and life-threatening [10]. The incidence of skin rash with LTG therapy in this study was 7.48%, which is lower than the reported rate, probably because of the low doses and slow titration.…”
Section: Discussioncontrasting
confidence: 53%
“…The incidence of skin rash with LTG therapy in this study was 7.48%, which is lower than the reported rate, probably because of the low doses and slow titration. The incidence of skin rash with LTG is doseand titration-dependent [10,14]. In this study, 6 males and 5 females developed CADR.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In particular, it is used to treat partial seizures and tonic-clonic convulsions. [10] It also acts as a mood stabilizer. Chemically unrelated to other anticonvulsants, it has relatively few side-effects and does not require therapeutic drug monitoring.…”
mentioning
confidence: 99%